The impact of caring for a school-going visually impaired child in Cape Town, Western Cape on the home caregiver and the rest of the family – the health, socio-economic and psychological health burdens - St. Jerry, Marlyse (Stellenbosch : Stellenbosch University, 2021)
Thesis (MSc)--Stellenbosch University, 2021.